Etiological Patterns and Clinical manifestations of Severe Anemia in Hospitalized Patients - Himavathy Kodandarao Gara; Dharma Rao Vanamali (Assam Journal of Internal Medicine)
Background: Severe anemia is a significant global health issue, particularly among hospitalized patients, with diverse etiologies and complex clinical presentations. This retrospective hospital-based study aimed to explore the prevalence, clinical manifestations, and etiological factors of severe anemia in hospitalized patients. Materials and Methods: Medical records of 103 patients admitted with severe anemia from February 2023 to January 2024 were analyzed. After exclusions, data from 85 patients were included in the final analysis.Results: The mean age of participants was 45.82 years, with a predominance of middle-aged and older individuals. Dyspnea was the most prevalent symptom, followed by giddiness and weight loss. Approximately one-fifth of patients had congestive heart failure, which was more common in older age groups. Hemoglobin levels ranged from 6.5 to 7.9 g/dL in 63% of patients, with microcytic hypochromic anemia being the most common peripheral blood smear finding. Nutritional deficiencies were the leading cause of severe anemia, followed by anemia of chronic disease (ACD), with iron deficiency anemia being the most prevalent subtype. ACD was predominantly seen in older age groups, while nutritional deficiencies were more common in younger patients and significantly higher in females. Gender disparities were evident, with males exhibiting a higher prevalence of ACD and females showing a higher prevalence of nutritional deficiency anemia. Conclusion: This study underscores the need for targeted interventions addressing nutritional inadequacies, disease-specific treatments, and gender-sensitive healthcare strategies to optimize patient outcomes. A comprehensive understanding and management of severe anemia are essential to mitigate its impact on morbidity and mortality, particularly among hospitalized patients.